2012
DOI: 10.3109/01612840.2012.728279
|View full text |Cite
|
Sign up to set email alerts
|

Changing Attitudes and Perceptions of Hispanic Men Ages 18 to 25 about Rape and Rape Prevention

Abstract: This exploratory study was designed to test the effectiveness of Foubert's intervention, The Men's Program, on a sample of 18- to 25-year-old Hispanic men who are not enrolled at a University or College. We explored participants' perceptions of, reactions to, and experience of the program. The information collected will be used to adapt the program to this specific population in order to increase cultural relevancy and specificity and create lasting attitudinal change. Three groups of six-eight Hispanic males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The studies showed that children and adolescents from 5 to 18 years old are able to learn certain first aid techniques. 10,11,[13][14][15][16][17][20][21][22][23][24][25][26][28][29][30][31][32][34][35][36][37]39 In addition, it was shown that children/adolescents from 11 to 18 years are willing to provide help, 12,18,19,27,33,38 and that first aid training is useful to increase their confidence or self-efficacy. 38 A strength of our project is that for the first time all the available evidence concerning the effectiveness of first aid training to children on knowledge, skills and attitudes, including evidence on their helping behaviour, is brought together into one document, which was used to develop an educational scheme based on current knowledge and practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies showed that children and adolescents from 5 to 18 years old are able to learn certain first aid techniques. 10,11,[13][14][15][16][17][20][21][22][23][24][25][26][28][29][30][31][32][34][35][36][37]39 In addition, it was shown that children/adolescents from 11 to 18 years are willing to provide help, 12,18,19,27,33,38 and that first aid training is useful to increase their confidence or self-efficacy. 38 A strength of our project is that for the first time all the available evidence concerning the effectiveness of first aid training to children on knowledge, skills and attitudes, including evidence on their helping behaviour, is brought together into one document, which was used to develop an educational scheme based on current knowledge and practice.…”
Section: Discussionmentioning
confidence: 99%
“…The major reason for exclusion was study design (56%) as many studies did not include a control group or performed a baseline measurement, or references were references were opinion pieces, letters, or comments. The 30 studies finally retained include 15 European studies (Austria, Norway, Spain, UK), 10-24 7 studies from the USA, [25][26][27][28][29][30][31] 3 studies from Australasia (Australia and New-Zealand), 32-34 2 African studies (Egypt and Zambia), 35,36 and 3 Asian studies (Japan, Pakistan, India). [37][38][39] Only for Rautek and fainting, no evidence could be identified.…”
Section: Study Identificationmentioning
confidence: 99%
“…Emphasizing active and enthusiastic involvement could help mitigate issues of ambiguity and complexity in consent communication (Harris, 2018). In addition, a number of rape-prevention studies suggest a shift to empathy-based programs, with an emphasis on teaching men how to prevent sexual violence and be supporters and allies for rape and sexual violence survivors (Langhinrichsen-Rohling et al, 2011; Lawson et al, 2012; Salazar et al, 2014; Stewart, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…By creating safe spaces for intimate dialogue, student-athletes can practice how they would intervene as an active bystander and respond to incidents of sexual assault involving their peers. In addition, curriculum on bystander intervention tailored to student-athletes could adopt a more culturally relevant model for diverse populations, which has shown positive increases in attitudes toward bystander intentions (Lawson et al, 2012).…”
Section: Discussionmentioning
confidence: 99%